2014
DOI: 10.1175/mwr-d-13-00142.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Cloud-Scale Lightning Data Assimilation Technique and a 3DVAR Method for the Analysis and Short-Term Forecast of the 29 June 2012 Derecho Event

Abstract: This work evaluates the short-term forecast (#6 h) of the 29-30 June 2012 derecho event from the Advanced Research core of the Weather Research and Forecasting Model (WRF-ARW) when using two distinct data assimilation techniques at cloud-resolving scales (3-km horizontal grid). The first technique assimilates total lightning data using a smooth nudging function. The second method is a three-dimensional variational technique (3DVAR) that assimilates radar reflectivity and radial velocity data. A suite of sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
103
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 79 publications
0
103
0
Order By: Relevance
“…In recent years, several studies have shown the positive impact that lightning assimilation has on the weather forecast and especially on the precipitation forecast (Alexander et al, 1999;Chang et al, 2001;Papadopulos et al, 2005;Mansell et al, 2007;Fierro et al, 2013;Giannaros et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, several studies have shown the positive impact that lightning assimilation has on the weather forecast and especially on the precipitation forecast (Alexander et al, 1999;Chang et al, 2001;Papadopulos et al, 2005;Mansell et al, 2007;Fierro et al, 2013;Giannaros et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Giannaros et al (2016) implemented a similar approach in the Weather Research and Forecasting (WRF) model, showing the positive and statistically robust impact of the lightning data assimilation on the 24 h rainfall forecast for eight convective events over Greece. Fierro et al (2013) and Qie et al (2014) introduced two lightning data assimilation schemes for the WRF model intervening on the mixing ratios of the hydrometeors (water vapour in the case of Fierro et al, 2013, and ice crystals, graupel and snow in Qie et al, 2014). Both studies, which are performed at cloud resolving scales, show that lightning assimilation improves the precipitation forecast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lightning data have also been used in models as a proxy for deep convection to improve parameters related to cold clouds and precipitation (Alexander et al 1999;Pessi and Bussinger 2009;Fierro et al 2012). Studies employing data assimilation (Alexander et al 1999;Pessi and Bussinger 2009;Fierro et al 2012) have utilized nudging techniques to improve forecasting and analysis for some extreme events.…”
Section: Introductionmentioning
confidence: 99%
“…Studies employing data assimilation (Alexander et al 1999;Pessi and Bussinger 2009;Fierro et al 2012) have utilized nudging techniques to improve forecasting and analysis for some extreme events. More recently, scientists have investigated the utility of lightning observations for identifying convective events at several spatial scales for which they conclude that the assimilation of lightning favorably impacts several model variables as well as initial conditions (Apodaca et al 2014;Fierro et al 2014).…”
Section: Introductionmentioning
confidence: 99%